1984
DOI: 10.1002/j.1551-8833.1984.tb05263.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chlorine Dioxide, Chlorine, Chlorite, and Chlorate in Water

Abstract: This article describes a procedure for either amperometric or potentiometric determination of iodine formed by the oxidation of iodide by chlorine dioxide, chlorine, chlorite, and chlorate. Either phenylarsine oxide or sodium thiosulfate can be used as the titrant. Sample pretreatment and pH adjustment are used to differentiate among the various chlorine species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 6 publications
1
81
0
3
Order By: Relevance
“…The reader is advised to consult the text by White (1992) and journal article written by Aieta et al (1984) for detailed information regarding chlorine dioxide generation rnethods and chemistry .…”
Section: Chlorine Dioxide Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…The reader is advised to consult the text by White (1992) and journal article written by Aieta et al (1984) for detailed information regarding chlorine dioxide generation rnethods and chemistry .…”
Section: Chlorine Dioxide Generationmentioning
confidence: 99%
“…In brief, chlorine dioxide is often generated through the reaction of aqueous sodium chlorite and chlorine (Aieta et al, 1984). In its US survey, Dietrich et al (1992) found that, for al1 of the 32 treatment utilities which responded, the generation of chlorine dioxide consisted of reacting aqueous chlorite (88.2% of the facilities reported using sodium chlorite in the generation process) with chlorine gas or hypochlorous acid.…”
Section: Chlorine Dioxide Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodometric titration registers all oxyhalides. 15 Only the HOCl and OCl À content is effective in killing microorganisms and dissolving protein. 16 It was considered important to investigate whether the amount of tissue dissolved by a solution affected the residual chlorine content and whether these measurements were useful in assessing the comparative effectiveness of NaOCl solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This is because iodometric titration for active chlorine registers them along with HOCl and OCl À . 15 Analysis of the ClO 3…”
Section: Introductionmentioning
confidence: 99%